2017
DOI: 10.1016/j.peptides.2017.04.011
|View full text |Cite
|
Sign up to set email alerts
|

A randomized cross-over study of the effects of macronutrient composition and meal frequency on GLP-1, ghrelin and energy expenditure in humans

Abstract: We found higher EE during 2.5h following one large drink compared with five smaller beverages. Since hunger was also suppressed more efficiently, and serum GLP-1 levels were higher after one compared with five smaller drinks, our findings do not support nibbling to avoid hunger or to keep up EE from morning to noon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Rizi et al [ 68 ] reported that a high-protein or high-fat meal suppresses ghrelin and induces more favorable postprandial satiety than that by a high-carbohydrate meal in insulin-resistant individuals. Low-carbohydrate drinks could decrease serum ghrelin levels after 2.5 h than those by high-carbohydrate drinks, and meal frequency also affects the sense of satiety [ 69 ]. However, Rock et al [ 70 ] showed that a nut-containing meal does not contribute to increased satiety due to gastrointestinal hormone response (including GLP-1, PYY, pancreatic polypeptide, cholecystokinin, and ghrelin).…”
Section: Role Of Ghrelin In the Regulation Of Energy Expenditurementioning
confidence: 99%
“…Rizi et al [ 68 ] reported that a high-protein or high-fat meal suppresses ghrelin and induces more favorable postprandial satiety than that by a high-carbohydrate meal in insulin-resistant individuals. Low-carbohydrate drinks could decrease serum ghrelin levels after 2.5 h than those by high-carbohydrate drinks, and meal frequency also affects the sense of satiety [ 69 ]. However, Rock et al [ 70 ] showed that a nut-containing meal does not contribute to increased satiety due to gastrointestinal hormone response (including GLP-1, PYY, pancreatic polypeptide, cholecystokinin, and ghrelin).…”
Section: Role Of Ghrelin In the Regulation Of Energy Expenditurementioning
confidence: 99%
“…Within minutes of consuming a meal containing carbohydrate and/or protein, both humans and rodents exhibit an increase in energy expenditure and body temperature, typically described as diet-induced or meal thermogenesis. In lean individuals, postprandial energy expenditure typically correlates positively with meal size (1, 2), protein and carbohydrate content (3)(4)(5)(6)(7)(8), and plasma insulin concentrations (9-13); however, most (12,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) but not all (4,9,(29)(30)(31) studies on this topic have indicated that meal thermogenesis -measured as energy expenditure -is diminished in obese individuals and have suggested that this reduction in meal thermogenesis may contribute to the pathogenesis of obesity by decreasing overall daily energy expenditure. Therefore, it is of great interest to understand the mechanism by which feeding increases body temperature and energy expenditure.…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid hormone levels were assessed, and confirmed to be normal, in all the participants ahead of participation. Results from 14 non-obese subjects have been reported [18]. For the results presented herein, 14 overweight or obese subjects were additionally recruited in order to study differences of the test meals in relation to baseline fasting insulin levels, i.e.…”
Section: Recruitment and Interventionsmentioning
confidence: 99%
“…All the test meals had a temperature of 18-22 °C. The total trial-period for recruitment and follow-up for all 28 subjects was from September 1, 2015 to April 31, 2016 [18]. All four test meals for each individual subject were ingested within a six weeks period.…”
Section: Recruitment and Interventionsmentioning
confidence: 99%
See 1 more Smart Citation